Simultaneous Quantification of Anandamide and Other Endocannabinoids in Dorsal Vagal Complex of Rat Brainstem by LC-MS - Chen, Jing (2009)
A quantitative method has been developed and validated for the simultaneous determination of anandamide (AEA), docosatetraenylethanolamide (DEA) and N-arachidonyldopamine (NADA) in dorsal vagal complex (DVC) of rat brainstem by liquid chromatographic-electrospray ionization mass spectrometry. The analytes were extracted from the tissue samples of rat brainstem by a single step liquid extraction technique using acetonitrile. The chromatographic separation was conducted on a C18 column using a gradient mobile phase consisting of methanol and water at a flow rate of 0.3 mL min(-1). The analytes were quantified by positive electrospray ionization mass spectrometry with selected ion monitoring (SIM) mode. The limits of detection (LOD) for AEA, DEA and NADA were 0.5, 1 and 0.5 ng mL(-1), respectively. This method required only simple processing of the samples and could be applied to monitor the change in the level of these compounds in DVC of the rat brain tissue. Time dependent (10-70 min) accumulation of the endocannabinoids (AEA, DEA, and NADA) in brain tissue was also studied, which included a novel examination of the accumulation of DEA as a function of time in rat brain tissue after decapitation.